Trade Liberalization and the Gender Employment Gap in China - Feicheng Wang; Krisztina Kis-Katos; Minghai Zhou (Institute of Labor Economics (IZA), 2020)
This paper investigates the impact of import liberalization induced labor demand shocks on male and female employment in China. Combining data from population and firm censuses between 1990 and 2005, we relate prefecture-level employment by gender to the exposure to tariff reductions on locally imported products. Our empirical results show that increasing import competition has kept more females in the workforce, reducing an otherwise growing gender employment gap in the long run. These dynamics were present both in local economies as a whole and among formal private industrial firms. Examining channels through which tariff reductions differentially affect males and females, we find that trade-induced competitive pressures contributed to a general expansion of female-intensive industries, a shift in sectoral gender segregation, reductions in gender discrimination in the labor market, technological upgrading through computerization, and general income growth.
Keywords: F13; F14; F16; F66; J16; 330; trade liberalization; import competition; gender employment gap; China